Pest Control Techniques for Hydroponic Plants in Palalang Village Pakong District Pamekasan Regency - Ilmi, Nurul; Luqman Al-Farisi, Bayuda (Program Studi Biologi Fakultas Matematika dan IPA Universitas Annuqayah, 2025)
Hydroponic plant cultivation is the main choice for young farmers. Hydroponics has many advantages compared to conventional farming. Pests/diseases are still a problem in hydroponic plant cultivation. Pest control in hydroponic plants cannot be relied on pesticides alone. This study aims to develop effective pest control techniques in hydroponic plants in Palalang Village, Pakong District, Pamekasan Regency. This study uses an experimental method with two treatments, namely pest control using pesticides and direct pest control, namely pest control by using hands directly to collect and destroy pests that attack plants. The results of the study showed that the combination treatment using pesticides and direct pest control can reduce the pest population and improve the quality and quantity of hydroponic plants. This technique has also been widely applied by the Pakong community and its surroundings, especially Palalang Village. Therefore, this pest control technique can be an effective alternative to control pests in hydroponic plants in Palalang Village, Pakong District, Pamekasan Regency.